SOFT CORAL Sinularia gibberosa EXTRACTS ORIGIN PALU BAY, CENTRAL SULAWESI WITH ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY - Muliadin Muliadin; Didit Kustantio Dewanto; Roni Hermawan; Putut Har Riyadi; Wendy Alexander Tanod (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2021)
Sinularia gibberosa is one of the soft coral species reported to produce bioactive compounds for pharmaceutical’s potential. Soft corals produce compounds with antibacterial and antioxidant properties. This study aimed to obtain a bioactive profile of S. gibberosa, which could scavenge DPPH radicals and inhibit the growth of Listeria monocytogenes, Pseudomonas aeruginosa, and Salmonella typhimurium. The research included a sampling of soft corals, extraction by maceration, identification of chemical profiles using LC-HRMS, the assay for antibacterial activity (well-diffusion method), antioxidant assay (DPPH method), and total phenolic content (Folin–Ciocalteu method). Sampling was conducted in Palu Bay, Central Sulawesi, Indonesia. Based on monomorphic colonies and sclerites, soft coral samples were identified as Sinularia gibberosa. The chemical profiles of S. gibberosa extracts was dominated by trimethylethanolamine (22.03%), arachidonic acid (14.13%), (3R)-3-hydroxy-4-(trimethylazaniumyl)-butanoate (10.90%), (5Z,8Z,11Z,14Z,16R)-16-Hydroxy-5,8,11,14-icosatetraenoic acid (5.64%), Octyl decyl phthalate (4.18%), and N-Methylnicotinic acid (3.63%). The antibacterial assaying at 300 mg/mL of S. gibberosa extracts showed moderate to strong antibacterial activity, with the inhibition zone diameter of L. monocytogenes (15.11 ± 0.70 mm), P. aeruginosa (13.44 ± 0.84 mm), and S. typhimurium (19.78 ± 0.39 mm). S. gibberosa extracts showed strong antioxidant activity, with an IC50 of 54.69 ± 0.34 µg/mL and total phenolic content was 5423.76 ± 14.00 mg GAE/25 mg dry extract. Based on the results, S. gibberosa shows the potential for antibacterial and antioxidant activity. This study indicates that soft corals origin Palu Bay, Central Sulawesi, Indonesia, are potential organisms in the discovery and development of antibacterial and antioxidant agents.